A Detailed Thermodynamic Description of Ion Pair Binding by a Calix[4]arene Derivative Containing Urea and Amide Functionalities - Marija Cvetnić; Tamara Rinkovec; Robert Vianello; Gordan Horvat; Nikola Bregović; Vladislav Tomišić (Molecules)
Receptors capable of binding both positive and negative ions are an important domain of supramolecular chemistry with valuable application potential. A Complete thermodynamic description of the equilibria related to ion pair recognition is beneficial in developing the optimized receptor systems, although it represents a difficult task that is rarely resolved due to various coupled processes. Here, we present a comprehensive study of ion pair (NaCl, NaHSO4, and NaH2PO4) binding by a ureido–amide calix[4]arene host in acetonitrile using a series of experimental techniques and molecular dynamics simulations. We devoted particular attention to characterizing the side processes (ion association and salt precipitation) and included them in the models describing ion pair complex formation. For this purpose, a multimethod approach (potentiometry, conductometry, ITC, flame AES) was employed, generating reliable data which provided insight into the thermodynamic effect of each included equilibrium. Positive cooperativity was observed in the context of NaCl and NaHSO4 binding by the studied calixarene. Computational results related to the NaCl complex in acetonitrile revealed that favorable Coulombic interactions, changes in affinity for solvent molecule inclusion, and intramolecular hydrogen bonding contributed to cation-induced cooperativity.